2016
DOI: 10.1038/nmat4785
|View full text |Cite
|
Sign up to set email alerts
|

High operational and environmental stability of high-mobility conjugated polymer field-effect transistors through the use of molecular additives

Abstract: . (2017) High operational and environmental stability of high-mobility conjugated polymer fieldeffect transistors achieved through the use of molecular additives. Nature Materials, 16 (3 Copies of full items can be used for personal research or study, educational, or not-for profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
390
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(410 citation statements)
references
References 31 publications
19
390
0
1
Order By: Relevance
“…5d) because of the traps. According to several studies 50, 51, 66 , we found that the polymer interaction with water results in an electrochemical oxidation of the polymer, while the interaction with the molecular oxygen gives rise to a formation of localized electron traps below the LUMO energy level. These findings extend to the case of ambipolar semiconductors 34, 67 and air-induced electron trapping in n-type polymer semiconductors 51 as reported in previous works, thus revealing that vacuum annealing is crucial to obtain ambipolar charge transport in PDPP3T.…”
Section: Resultsmentioning
confidence: 94%
“…5d) because of the traps. According to several studies 50, 51, 66 , we found that the polymer interaction with water results in an electrochemical oxidation of the polymer, while the interaction with the molecular oxygen gives rise to a formation of localized electron traps below the LUMO energy level. These findings extend to the case of ambipolar semiconductors 34, 67 and air-induced electron trapping in n-type polymer semiconductors 51 as reported in previous works, thus revealing that vacuum annealing is crucial to obtain ambipolar charge transport in PDPP3T.…”
Section: Resultsmentioning
confidence: 94%
“…Their molecular structures are shown in Figure 1b. This solution‐processed polymer/small‐molecule composite can act as an effective active layer for enabling high environmental/operational stability and good uniformity of OFETs 34. As one of key elements of the OFETs, the gate dielectric was solution processed by combining a thick polyelectrolyte film of hydrophilic PAA with a thin insulator layer of lipophilic PMMA.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that the ambient-induced asymmetry could be caused by water molecules trapped in voids in the AL. Water molecules have been recently reported to induce traps in conjugated polymers for field-effect transistors, 31 while oxidation of PCBM is known to also induce traps. 32 A third possibility is that ambient exposure leads to a degradation of the lamination interface, where a region of electron traps is formed, blocking the extraction of electrons generated in AL1.…”
Section: Resultsmentioning
confidence: 99%